Psycholinguistic Aspects of Lexical and Semantic Transformations While Translating The Ukrainian Week Articles - Povkh, Viktoria; Zasiekin, Serhii (East European Journal of Psycholinguistics, 2018)
Among the main goals of the study were to identify the psycholinguistic features of translating The Ukrainian Week’s articles into English. One interesting finding is that the translating process inevitably involves using lexical and semantic transformations brought to life both by the  features of source and target language systems and their stylistic characteristics. Another important finding was that the translation is a process of cognitive information processing. Accordingly, we can infer the stages of cognitive processes used by the translator during translation activity. This result may be explained by the fact that the use of lexical transformations requires sociocultural translation competence, extralinguistic or background knowledge of both languages and cultures. This observation may support the hypothesis that sociocultural competence affects the formation of individual consciousness in a direct way. It is possible, therefore, that the translator also carries out linguistic activity by creating the target text from the psychological point of view. Language as a means of communication implies an essential mechanism and takes a significant place in human cognition. A possible explanation for this might be that the essence of translation is to create additional links between the linguistic and psychological components in two languages.References  Alekseeva, I. S. (2001). Professionalnyi Trening Perevodchika. [Professional Training of Translator]. S.-Petersburg: Soyuz.Arnold, I. V. (2002). Stilistika. Sovremennyi Angliyskiy Yazyk. [Stylistics. Modern English]. Moscow: Flinta.Bakhtin, M. M. (1979). Estetika Slovesnogo Tvorchestva. [Aesthetics of Verbal Creativity]. Moscow: Iskusstvo.Zasiekina, L., Zasiekin, S. (2002). Vstup do Psykholingvistyky. [Introduction to Psycholinguistics]. Ostroh: Ostroh Academy.Karaban, V. I. (2001). Pereklad Angliyskoyi Naukovoyi i Tekhnichnoyi Literatury. [Translation of Scientific and Technical Literature]. Vinnyntsia: Nova Knyha.Maksimov, S. (2010). Praktychnyi Kurs Perekladu [Practical Course of Translation]. Kyiv: Lenvit.Retsker, Ya. (1973) Posobie po Perevody s Angliyskogo Yazyka na Russkiy. [Translation Manual from English into Russian]. Leningrad: Prosveshcheniye.Sourceshttps://tyzhden.ua/Politics/147037https://ukrainianweek.com/Columns/50/150213https://tyzhden.ua/Politics/217683https://ukrainianweek.com/Politics/217874http://tyzhden.ua/publication/215060https://ukrainianweek.com/Politics/215969tyzhden.ua/publication/218333https://ukrainianweek.com/World/218772https://tyzhden.ua/World/45554http://ukrainianweek.com/World/46045https://tyzhden.ua/World/218615http://ukrainianweek.com/World/219714http://tyzhden.ua/History/216348http://ukrainianweek.com/History/218867